2011
DOI: 10.1007/s11999-011-1866-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Fixation Stiffness Affects Healing by Differential Cartilage Formation in a Rat Osteotomy Model

Abstract: Background Dynamization involves a reduction in fixation construct stiffness during bone healing, allowing increased interfragmentary movement of the fracture through physiologic weightbearing and muscle contraction. Within some optimal range, interfragmentary movement stimulates healing, but this range likely varies across stages of bone healing. Questions/purposes How does the time of dynamization affect the cartilage formation, bony bridging, and bone resorption in a rat fracture-healing model? Methods Unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Samples were sectioned in the longitudinal direction and stained with paragon (Willie et al. 2011). Quantitative histomorphometry was performed using light microscopy in a region of interest (ROI) that included the complete outer diameter of the periosteal callus in the radial direction and extended 2 mm proximally and distally from the center of the gap.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were sectioned in the longitudinal direction and stained with paragon (Willie et al. 2011). Quantitative histomorphometry was performed using light microscopy in a region of interest (ROI) that included the complete outer diameter of the periosteal callus in the radial direction and extended 2 mm proximally and distally from the center of the gap.…”
Section: Methodsmentioning
confidence: 99%
“…A mechanical stimulation has also recently been investigated using a massage-like compression to enhance muscular healing with positive results [24]. The idea of a change in fixation stability, even though investigated for some time now in a research setting has so far not reached the clinic [25][26][27][28]. More often the change in the fixation regime is dictated by an unsatisfactory healing progression [29].…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical loading of a fracture callus occurs most commonly as a consequence of weight bearing; however, dynamization, or applied micromotion, of the fracture gap has also been investigated. Results of these studies have shown that the effects of loading depend heavily on the mode [39-42] , rate [43,44] , and magnitude of loading [45,46] , as well as gap size [45] and the time during healing at which the dynamization is enacted [47][48][49][50] . Application of cyclic compressive displacements can enhance healing through increased callus formation and more rapid ossifi cation and bridging [51,52] .…”
Section: Mechanobiology Of Fracture Healingmentioning
confidence: 99%
“…However, the benefi ts of applied cyclic compressive displacements appear to be limited to displacements that induce an interfragmentary strain (defi ned as the ratio of applied displacement to the gap size) of 7% or less [39,45,54,55] . Moreover, dynamization of the fracture gap appears to be detrimental in the very early stage of healing [47] yet benefi cial during later stages [48][49][50] . As evidenced by the success of distraction osteogenesis in both experimental and clinical settings, application of successive tensile displacements across an osteotomy gap can also promote bone formation.…”
Section: Mechanobiology Of Fracture Healingmentioning
confidence: 99%